Mental Health among Elite Track and Field Athletes in Iceland in Relation to Training Volume and Injuries - Dóróthea Jóhannesdóttir 1994- (2018)
Mental health among athletes has gained more attention in recent years. Studies have shown that prevalence of anxiety and depressive symptoms are similar among athletes as reported for the general public. However, training volume and injuries have not been studied simultaneously. Thus, the aim of the current study was to examine the prevalence of anxiety and depressive symptoms as well as sleep quality among elite track and field athletes in Iceland in relation to training volume and injuries. From 65 eligible, 41 athletes participated in the study, both males (51.2%) and females (48.8%). Participants answered a questionnaire including questions on sleep, depressive and anxiety symptoms as well as questions concerning background information. The results of the study showed that 31.7% of the athletes had mild to moderate symptoms of depression, 34% had mild to moderate anxiety symptoms and 14.6% had bad sleep quality. Although significant differences were not found between genders, females reported higher means for symptoms of depression and anxiety as well as poorer sleep quality than males. Additionally, the results showed that injured athletes reported significantly higher means for symptoms of depression and anxiety than athletes free of injury. Training volume did not affect symptoms of anxiety, depressive symptoms or sleep quality. Keywords: mental health, track and field, athletes, anxiety, depression, sleep quality, training volume, injury Andleg líðan meðal íþróttafólks hefur aukist í umræðu síðast liðin ár. Rannsóknir hafa sýnt að hlutfall kvíða- og þunglyndiseinkenna eru jafn algeng meðal íþróttafólks og almennings. Núverandi rannsókn var framkvæmd í þeim tilgangi að meta algengi kvíða- og þunglyndiseinkenna ásamt svefngæðum frjálsíþróttafólks í fremsru röð á Íslandi, í tengslum við æfingaálag og meiðsli. Samtals tóku 41 einstaklingur þátt í könnuninni, bæði karlar og konur. Þátttakendur svöruðu spurningalista sem innihélt spurningar um svefn, þunglyndis- og kvíðaeinkenni sem og spurningar um ...